The genus Polemistus de Saussure in China with descriptions of four new species (Hymenoptera: Crabronidae) - Ma, Li; Li, Qiang (Zootaxa, 2020)
The genus Polemistus de Saussure (Crabronidae: Pemphredoninae: Pemphredonini) from China is reviewed and a key to the Chinese species is provided. Four new species, Polemistus clypeisinuatus and Polemistus gutianus from Zhejiang Province, and Polemistus divaricatus and Polemistus pediflavidus from Yunnan Province are described and illustrated.